(untitled) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2016)
We describe the treatment of a young girl age, 18 years, with Class I malocclusion with anterior crowding and lock bite of two upper lateral incisors. The patient was treated by opening of space for lateral incisors with open coil spring with standard edgewise technique. The treatment resulted in Class I molar relation with proper alignment of both upper and lower anterior segment, an ideal overjet, overbite and incisor angulations. Ban J Orthod & Dentofac Orthop, April 2016; Vol-6 (1-2), P.35-41